(untitled) (MAUSAM, 1988)
Urbanization and industrialization change precipitation characteristics by modifying the local climate and generally increasing precipitation and precipitation related activity. Multivariate statistical tests are used in this study to detect the significance of changes in mean values of precipitation in urban areas. These tests are useful to simultaneously analyze the data from a number of stations in a region and to arrive at inferences about changes in precipitation in urban areas. The spatial correlation structure of multivariate data enables better quantification of the effects of urbanization on precipitation than analysis of data from single stations. The T2 test and test based on the analysis of variance are used in the present study to test the significance of changes in precipitation mean values. Annual precipitation data from several stations in the La Porte, St. Louis, Tulsa and Kansas city areas in the United States are analyzed and the results are presented.